2018
DOI: 10.1017/s0021859618001156
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary supplementation of guanidino acetic acid on growth performance, thigh meat quality and development of small intestine in Partridge-Shank broilers

Abstract: The current experiment aimed at assessing the effects of dietary supplementation of guanidino acetic acid (GAA) on growth performance, thigh meat quality and development of small intestine in broilers. A total of 360 1-day-old female broiler chicks were distributed randomly to four groups of 90 birds each, and each group received GAA dosages of 0, 0.4, 0.8 and 1.2 g/kg of feed dry matter. During the whole experiment of 60 days, broilers had ad libitum access to water and feed and the feed intake was recorded d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 30 publications
0
7
1
Order By: Relevance
“…So we can assume that the level of Arg was good enough in the diets with or without GAA supplemented to fulfil all metabolic roles, including gut maintenance. This finding is in contrast with some latest reports which showed that GAA supplementation caused better development of the small intestine, particularly greater height and width of intestinal villi (Ahmadipour et al 2018;Ren et al 2018).…”
Section: Resultscontrasting
confidence: 89%
See 1 more Smart Citation
“…So we can assume that the level of Arg was good enough in the diets with or without GAA supplemented to fulfil all metabolic roles, including gut maintenance. This finding is in contrast with some latest reports which showed that GAA supplementation caused better development of the small intestine, particularly greater height and width of intestinal villi (Ahmadipour et al 2018;Ren et al 2018).…”
Section: Resultscontrasting
confidence: 89%
“…Ale Saheb Fosoul et al (2018) showed that a reduction in the energy content of the diet decreased jejunal villus height and crypt depth. Although the mode of action for GAA on intestinal morphology has been proposed by some recent papers (Ahmadipour et al 2018;Ren et al 2018), information and data about the issue especially related to GAA and energy interactions are very limited in poultry, and most of the studies has addressed the role of Arg in relation to gut morphology and function. In the present study, birds fed the diet containing GAA had lower villus width and surface area.…”
Section: Resultsmentioning
confidence: 99%
“…Supplementation with GAA can spare the endogenous synthesis of GAA by arginine and glycine; thus more arginine and glycine can be used for the synthesis of proteins or endogenous amino acids to promote the growth of the body 5,6 . It has been reported that GAA supplementation improved growth performance and meat quality of pigs and broilers 4,7 . The addition of GAA also increased the creatine and arginine content.…”
Section: Introductionmentioning
confidence: 99%
“…The water-holding capacity of the thigh muscles was estimated using drip loss, and the drip loss was determined as described by Ren et al . (2019). Thigh muscles were trimmed to 5 cm × 3 cm × 1 cm and blotted to remove the surface water.…”
Section: Methodsmentioning
confidence: 99%
“…In this trial, the tenderness of the uncooked thigh muscles was estimated using the shear force value as described by Ren et al . (2019). Before measurement, the thigh muscles were split into strips with size of 3.0 cm × 1.0 cm × 0.5 cm parallel to the muscle fibre.…”
Section: Methodsmentioning
confidence: 99%